Dust energy balance study of two edge-on spiral galaxies in the Herschel-ATLAS survey - De Geyter, G.; Baes, M.; De Looze, I.; Bendo, G.J.; Bourne, N.; Camps, P.; Cooray, A.; De Zotti, G.; Dunne, L.; Dye, S.; Eales, S.A.; Fritz, J.; et al. (Oxford University Press, 2015)
Interstellar dust in galaxies can be traced either through its extinction effects on the star light or through its thermal emission at infrared wavelengths. Recent radiative transfer studies of several nearby edge-on galaxies have found an apparent inconsistency in the dust energy balance: the radiative transfer models that successfully explain the optical extinction underestimate the observed fluxes by an average factor of 3. We investigate the dust energy balance for IC 4225 and NGC 5166, two edge-on spiral galaxies observed by the Herschel Space Observatory in the frame of the H-ATLAS survey. We start from models which were constrained from optical data and extend them to construct the entire spectral energy distribution of our galaxies. These predicted values are subsequently compared to the observed far-infrared fluxes. We find that including a young stellar population in the modelling is necessary as it plays a non-negligible part in the heating of the dust grains. While the modelling approach for both galaxies is nearly identical, we find two very different results. As is often seen in other edge-on spiral galaxies, the far-infrared emission of our radiative transfer model of IC 4225 underestimates the observed fluxes by a factor of about 3. For NGC 5166 on the other hand, we find that both the predicted spectral energy distribution as well as the simulated images match the observations particularly well. We explore possible reasons for this difference and conclude that it is unlikely that one single mechanism is the cause of the dust energy balance problem in spiral galaxies. We discuss the different approaches that can be considered in order to get a conclusive answer on the origin this discrepancy.